PENERAPAN ITIL V3 DALAM EVALUASI CONTINUAL SERVICE IMPROVEMENT STUDI KASUS PADA PERUSAHAAN JASA TEKNIK - Henny Hartono; Yanthi Carolina; Honni Honni; William Wijaya; Johanes Fernandes Andry (Infotech: Journal of Technology Information, 2026)
The rapid development of information technology requires every organization, including engineering service companies, to provide quality, reliable, and sustainable services. However, in practice, various obstacles are often found, such as service delays, lack of standard documentation, and weak monitoring of IT service quality. This condition indicates the need for a systematic evaluation of information technology service management in order to achieve continuous improvement. One framework widely used internationally to support IT service quality improvement is ITIL V3. This research is motivated by the need for an evaluation method that is able to measure the level of CSI maturity in engineering service companies, while also providing an overview of the gap between actual conditions. Thus, the results of the study are expected to provide not only practical improvement recommendations for the research object, but also theoretical contributions in the development of CSI-based IT service governance evaluation methods. The main objective of the research is to evaluate the maturity level based on the ITIL V3 standard in engineering service companies. The proposed research method stages include several main steps, namely a literature study conducted to review previous theories and research related to ITIL V3 and CSI, the data collection stage through interviews, observations, to related parties in the Engineering services company, analysis of service maturity levels using the maturity level model, comparison of evaluation results to identify gaps. Fifth, the preparation of strategic recommendations in the form of a continuous improvement plan that can be implemented. The results of the study are a level of conformity of 1 to 3 with 4 parameters that meet the standards. Of the 31 parameters at each level, 9 received a maturity value of 1, 18 received a maturity value of 2, and no parameters received a maturity value of 4 or 5.